Mammography and breast tomosynthesis simulator for virtual clinical trials - Badal, Andreu; Sharma, Diksha; Graff, Christian G.; Zeng, Rongping; Badano, Aldo (Computer physics communications, 2021)
Computer modeling and simulations are increasingly being used to predict the clinical performance of x-ray imaging devices in silico, and to generate synthetic patient images for training and testing of machine learning algorithms. We present a detailed description of the computational models implemented in the open source GPU-accelerated Monte Carlo x-ray imaging simulation code MC-GPU. This code, originally developed to simulate radiography and computed tomography, has been extended to replicate a commercial full-field digital mammography and digital breast tomosynthesis (DBT) device. The code was recently used to image 3000 virtual breast models with the aim of reproducing in silico a clinical trial used in support of the regulatory approval of DBT as a replacement of mammography for breast cancer screening. The updated code implements a more realistic x-ray source model (extended 3D focal spot, tomosynthesis acquisition trajectory, tube motion blurring) and an improved detector model (direct-conversion Selenium detector with depth-of-interaction effects, fluorescence tracking, electronic noise and anti-scatter grid). The software uses a high resolution voxelized geometry model to represent the breast anatomy. To reduce the GPU memory requirements, the code stores the voxels in memory within a binary tree structure. The binary tree is an efficient compression mechanism because many voxels with the same composition are combined in common tree branches while preserving random access to the phantom composition at any location. A delta scattering ray-tracing algorithm which does not require computing ray-voxel interfaces is used to minimize memory access. Multiple software verification and validation steps intended to establish the credibility of the implemented computational models are reported. The software verification was done using a digital quality control phantom and an ideal pinhole camera. The validation was performed reproducing standard bench testing experiments used in clinical practice and comparing with experimental measurements. A sensitivity study intended to assess the robustness of the simulated results to variations in some of the input parameters was performed using an in silico clinical trial pipeline with simulated lesions and mathematical observers. We show that MC-GPU is able to simulate x-ray projections that incorporate many of the sources of variability found in clinical images, and that the simulated results are robust to some uncertainty in the input parameters. Limitations of the implemented computational models are discussed. Program title: MCGPU_VICTRE CPC Library link to program files:https://doi.org/10.17632/k5x2bsf27m.1 Licensing provisions: CC0 1.0 Programming language: C (with NVIDIA CUDA extensions) Nature of problem: The health risks associated with ionizing radiation impose a limit to the amount of clinical testing that can be done with x-ray imaging devices. In addition, radiation dose cannot be directly measured inside the body. For these reasons, a computational replica of an x-ray imaging device that simulates radiographic images of synthetic anatomical phantoms is of great value for device evaluation. The simulated radiographs and dosimetric estimates can be used for system design and optimization, task-based evaluation of image quality, machine learning software training, and in silico imaging trials. Solution method: Computational models of a mammography x-ray source and detector have been implemented. X-ray transport through matter is simulated using Monte Carlo methods customized for parallel execution in multiple Graphics Processing Units. The input patient anatomy is represented by voxels, which are efficiently stored in the video memory using a new binary tree structure compression mechanism.